Intestinal morphograhy of broilers fed diets supplemented with perlite - GHIASI GHALEHKANDI, J.; HASSANPOUR, S.; EBRAHIMNEHZAD, Y.; BEHESHTI, R.; MAHERI-SIS, N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Aim of the study was to investigate effects of different levels of perlite on intestinal morphometry in broilers (Ross 308). A hundred and eighty broiler cockerels were randomly allocated into three experimental groups (3 replications and 20 broilers per pen) and fed experimental diets supplemented with different levels of perlite (0%, 2%, 4%). At 21, 28, 35 and 42 days of the study, 2 broilers were randomly selected from each replication, slaughtered and various sections of small intestine (1, 10, 30, 50, 70 and 90% of small intestine length) sampled for morphometry characteristics. Villi height, crypts depth and villus height / crypt depth ratio were measured microscopically. According to the results, a significant difference was observed on small intestine morphology post-perlite supplementation in experimental groups compared to control group. Supplementation of diet with perlite (2%) significantly increased average villi height in various sections of small intestine (1, 70 and 90%) in experimental birds on days 28 and 35 (P < 0.05). In addition, similar findings were observed after addition of perlite (4%) on villi height on day 42 (P <0.05). Furthermore, on day 28, average villi height and depth of liberkuhn crypts in small intestine (10%) differed significantly in cockerels fed diets containing 2% perlite in comparison to controls (P < 0.05). These results suggest that supplementation of perlite in broilers’ diet can improve intestinal morphometry.